2019
DOI: 10.1093/brain/awz296
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal alpha-synuclein fibrils in monkeys: spreading, imaging and neuropathological changes

Abstract: See Dehay and Bezard (doi:10.1093/brain/awz329) for a scientific commentary on this article. Intrastriatal injections of fibrillar α-synuclein in rodents have been shown to induce a Parkinson’s disease-like spreading of Lewy body pathology. Chu et al. inject exogenous α-synuclein pre-formed fibrils into the putamen of non-human primates, and observe spreading of pathology, nigrostriatal degeneration, and dopamine transporter upregulation indicative of early Parkinson’s disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 67 publications
8
76
0
1
Order By: Relevance
“…The stereotypic spread of Lewy bodies in PD from the rostral brain stem to the midbrain and eventually throughout the neocortex suggests a prion-like mechanism mediating propagation of protein aggregates from neuron to neuron [5]. This temporo-spatial spread of Lewy bodies correlates with clinical progression of PD and has been replicated in several animal models [6][7][8].…”
Section: Introductionmentioning
confidence: 84%
“…The stereotypic spread of Lewy bodies in PD from the rostral brain stem to the midbrain and eventually throughout the neocortex suggests a prion-like mechanism mediating propagation of protein aggregates from neuron to neuron [5]. This temporo-spatial spread of Lewy bodies correlates with clinical progression of PD and has been replicated in several animal models [6][7][8].…”
Section: Introductionmentioning
confidence: 84%
“…Subsequently, the aggregation of monomers into fibrils is induced and the fibrils are sonicated to generate short fibrils w h i c h a f t e r i n j e c t i o n , t r i g g e r t h e a g g r e g a t i o n , hyperphosphorylation and ubiquitination of endogenous a-Syn (Patterson et al, 2019). Intracerebral injection of a-Syn PFFs has been extended to rodents, both mice (Luk et al, 2012a;Masuda-Suzukake et al, 2013;Karampetsou et al, 2017;Milanese et al, 2018;Okuzumi et al, 2018;Patterson et al, 2019) and rats (Paumier et al, 2015;Harms et al, 2017;Thakur et al, 2017;Duffy et al, 2018b;Durante et al, 2019) and non-human primates (Shimozawa et al, 2017;Chu et al, 2019). PFFs have been mainly injected in the striatum (Luk et al, 2012a;Paumier et al, 2015;Karampetsou et al, 2017;Shimozawa et al, 2017;Duffy et al, 2018b;Milanese et al, 2018;Okuzumi et al, 2018;Chu et al, 2019;Durante et al, 2019;Patterson et al, 2019), the substantia nigra (Masuda-Suzukake et al, 2013;Harms et al, 2017) and the cortex (Luk et al, 2012b).…”
Section: Injection Of A-syn Pre-formed Fibrils or Pathological Extractsmentioning
confidence: 99%
“…It is well described that intracerebral inoculation of PFFs leads to the formation of pa-Syn-immunoreactive aggregates that are distributed both in the soma and neuronal processes. a-Syn inclusions exhibit different morphological features that resemble human Lewy bodies: from granules with cytoplasmic staining to compact and rounded structures with dark staining that fills entirely cells (Luk et al, 2012a;Paumier et al, 2015;Chu et al, 2019). Some studies have shown that these aggregates commonly colocalize with key markers of Lewy bodies, including ubiquitin and p62/proteasome 1 (Wakabayashi et al, 2013), and they are thioflavin S-positive and proteinase K-resistant, indicating that they share common properties with human Lewy bodies (Paumier et al, 2015;Chu et al, 2019).…”
Section: Injection Of A-syn Pre-formed Fibrils or Pathological Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…This PFF injection induced the formation of α-syn-positive cytoplasmic inclusions in neurons of the striatum as well as interconnected regions such as the cortex, associated with a loss of dopaminergic neurons in the SN and motor dysfunctions [60], while a similar injection of soluble α-syn had no effect [61]. PFF also induced a progressive synucleinopathy after intracerebral injection into susceptible transgenic mice [62][63][64], and in non-human primate models [65]. In 2014, LB-enriched fractions purified from PD brains containing pathological aggregated α-syn were injected unilaterally in the SN and striatum of WT mice and non-human primates.…”
Section: The Prion-like Hypothesis As a Model Of α-Syn Pathogenicitymentioning
confidence: 96%